Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174115
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Libet Clock

Abstract: The Sense of Agency (SoA) refers to our capability to control our own actions and influence the world around us. Recent research in HCI has been exploring SoA to provide users an instinctive sense of "I did that" as opposed to "the system did that". However, current agency measurements are limited. The Intentional Binding (IB) paradigm provides an implicit measure of the SoA. However, it is constrained by requiring high visual attention to a "Libet clock" onscreen. In this paper, we extend the timing stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 73 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…Letters were either 250 ms, 500 ms, or 750 ms long (for more detail see Apparatus and stimuli). According to the study by Cornelio Martinez et al (2018), we expected to find temporal binding in the 250 ms condition. Additionally, we were interested to find out how variations in the interval length influence temporal binding as an objective measure.…”
Section: Experiments 1: Manipulation Of Interval Lengthmentioning
confidence: 97%
See 1 more Smart Citation
“…Letters were either 250 ms, 500 ms, or 750 ms long (for more detail see Apparatus and stimuli). According to the study by Cornelio Martinez et al (2018), we expected to find temporal binding in the 250 ms condition. Additionally, we were interested to find out how variations in the interval length influence temporal binding as an objective measure.…”
Section: Experiments 1: Manipulation Of Interval Lengthmentioning
confidence: 97%
“…To reduce the task's inherent visual load and to introduce more flexibility in the experimental task, Cornelio Martinez, Maggioni, Hornbaek, Obrist, and Subramanian (2018) proposed an "auditory Libet Clock." This method uses spoken letters, which are presented over headphones, rather than the visual clock hand to determine the perceived timing of the actions or events.…”
Section: Introductionmentioning
confidence: 99%
“…All data and statistical analyses were conducted using MAT-LAB (v. R2012a, MathWorks, Natick, MA) and IBM SPSS Statistics (v. 22 and 23;2014, 2018. The results of the Kolmogorov-Smirnov test indicated that all but two factors were normally distributed.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The Libet clock rotated clockwise once every 2560ms, its size was 500 pixels, shown on a screen of 24-inch, 1920 x 1200 in resolution. The numbers of the clock were removed in order to avoid creating visual patterns during the task [21,22]. Instead, after each trial when the dot stopped, participants used a rotational controller (Griffin Powermate Knob) to relocate the dot on their perceived position.…”
Section: Intentional Binding (Ib) Task Proceduresmentioning
confidence: 99%